Penyuluhan Pembuatan Jamu Kunyit Asam Dan Jamu Empon-Empon Dalam Meningkatkan Imunitas Tubuh Masyarakat Di Daerah Puskesmas Tiban Baru - Delladari Mayefis; Suci Fitriani Sammulia; Siska Widiastuti; Dwi Puspa Meileni (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2022)
Immunity is the main choice for people to protect themselves from the Covid-19 pandemic which has caused the Indonesian people to experience a decline in health. To increase the body’s immunity one of them is using traditional medicine (herbal). The use of herbal medicine is an Indonesian ancestral heritage that is obtained empirically and from generation to generation. Herbal medicine is a nutritious and safe drink to increase the body’s immunity during the covid-19 pandemic. The method used is counseling to the community and making herbal medicine in the new tiban health center area in increasing body immunity.